Preoperative Posterior Segment Evaluation by Ultrasonography in Dense Cataract - Ziauddin A. Shaikh, Faheem Ullah Shaikh, Ashok Kumar Narsani , Shafi Muhammad Jatoi (Pakistan Journal of Ophthalmology, 2009)
Purpose: Ultrasonography is an important tool for evaluating the posterior segment in eyes with opaque media. Material and Method: The study was conducted in the Department of Ophthalmology, Civil Hospital Karachi from October 2005 to March 2006. In this study evaluation of two hundred and twenty seven eyes of 200 patients with dense cataract precluding visualization of fundus underwent examination by standardized B scan ultrasonography. Presence of certain ocular risk factors believed to be associated with a high incidence of abnormal posterior segment on ultrasound was looked for. Result:Two hundred and twenty seven eyes of two hundred patients were included in the study. Twenty-seven patients had bilateral cataract and 6 patients were only eyed. Age range was 43 to 81 years with a mean age of 51 years. One hundred and sixteen (58%) patients were male and 84 (42%) females. On B-Scan ultrasonography 18 (7.90%) eyes had finding suggestive of posterior segment pathology. The most common finding was posterior staphyloma in 8 (3.52%) eyes. Out of the 200 patients 163 (81.5%) had no risk factor for abnormal posterior segment on ultrasonography, while 37 (18.5 %) were associated with systemic and ocular risk factors, among them diabetes, hypertension and early age, posterior synechiae, elevated intraocular pressure and keratic precipitates were frequently seen. Conclusion: Preoperative posterior segment evaluation with ultrasound in patients with dense cataract can be used to detect pathologies that may influence the surgical strategy and the postoperative visual prognosis